2021
DOI: 10.2196/29098
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Factors Influencing Engagement With Health and Well-being Apps in the United Kingdom: Qualitative Interview Study

Abstract: Background Digital health devices, such as health and well-being smartphone apps, could offer an accessible and cost-effective way to deliver health and well-being interventions. A key component of the effectiveness of health and well-being apps is user engagement. However, engagement with health and well-being apps is typically poor. Previous studies have identified a list of factors that could influence engagement; however, most of these studies were conducted on a particular population or for an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 41 publications
3
30
0
Order By: Relevance
“…A faulty app that presents errors or bugs to the user can also have a negative impact in user engagement ( 63 ). In line with previous findings, the existence of human support is a critical aspect of digital interventions and reinforces the importance of the therapeutic alliance even in digital interventions ( 64 , 65 ). Also, credibility can lead to more engaged users if the app incorporates expertise or clinician encouragement ( 21 ).…”
Section: Discussionsupporting
confidence: 90%
“…A faulty app that presents errors or bugs to the user can also have a negative impact in user engagement ( 63 ). In line with previous findings, the existence of human support is a critical aspect of digital interventions and reinforces the importance of the therapeutic alliance even in digital interventions ( 64 , 65 ). Also, credibility can lead to more engaged users if the app incorporates expertise or clinician encouragement ( 21 ).…”
Section: Discussionsupporting
confidence: 90%
“…In line with these findings, our intervention included morning and evening check-ins and personalization of content. Users received customizable notification-type reminders—a feature that has been identified as useful for engagement with digital health interventions [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our achievement of high user retention and engagement with a CA-based, pain-customized, digital mental health intervention has clear implications for addressing issues of suboptimal engagement with digital health interventions and of improving access to care for chronic pain. Research indicates that people with chronic pain are almost twice as likely to drop out from self-guided digital interventions when compared to traditional, guided interventions [ 21 ]. Despite this, the present trial achieved high levels of retention and engagement among a sample of individuals with chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies with shorter follow-up periods have identified that factors such as health literacy, motivation, capabilities, social and environmental structures, and social support have an impact on mHealth engagement [ 51 , 52 ]. However, this study shows that patients’ motivation, capability, and social and environmental factors change over time.…”
Section: Discussionmentioning
confidence: 99%